Prevalence of Second Victim Experiences in a Cohort of Healthcare Learners and the Impact on Their Well-Being - Vanessa E. Torbenson; Kirsten A. Riggan; Cynthia M. Stonnington; Lily Huang; Abd Moain Abu Dabrh; Adam I. Perlman; Tyler F. Vadeboncoeur; Megan A. Allyse; Robyn E. Finney; Enid Y. Rivera-Chiauzzi (Journal of Medical Education and Curricular Development)
Objectives This study identified the prevalence of second victim experience (SVE) in a multidisciplinary sample of healthcare learners and explored personal experiences of trauma and desired forms of support following traumatic patient care events or situations. Method We used the validated SVE Support Tool-Revised and the Physician Well-Being Index (PWBI) to query healthcare learners at a large academic health system across the institution's medical, graduate medical education, and health sciences schools. The survey was open to all healthcare learners from April 8th, 2022 to May 30th, 2022. Here, we report on an analysis of respondents’ fixed responses describing the prevalence and characteristics of SVE. Results Of 2298 potential respondents, 206 answered at least one question (9.0% response rate). Of the 206 respondents, 205 answered questions inquiring if they had been a part of a stressful or traumatic patient care event or situation and 54.1% (111/205) answered in the affirmative. Of this group, 49.5% (51/103) reported feeling like a second victim (SV). The average PWBI of the exposed group was significantly higher (worse well-being) than the nonexposed group (3.4 vs 2.6, P  = .0009). The most common forms of desired support for those exposed to a traumatic event and felt like an SV was conversation with peers 95.3% (41/43), family 81.4% (35/43), and a supervisor or manager 67.4% (29/43). Conclusion Findings suggest that many healthcare learners experience SVE and would benefit from connection to desired support strategies. Strategies to mitigate the impact of SVE on professional self-efficacy should be considered by education administrators. We present strategies from the literature and our institution that may be replicated for early identification and support of learners with SVE.